SEROPREVALENCIA DE LA CISTICERCOSIS PORCINA EN TRES CASERÍOS DE LA PROVINCIA DE ANDAHUAYLAS, APURÍMAC - Ayvar P., Viterbo (2004)
Porcine cysticercosis is endemic in rural communities of Peru, due to prevaling conditions contributing to the occurrence, transmission and maintenance of the disease. This paper assessed the real prevalence of porcine cysticercosis in three villages of Andahuaylas province, Apurímac. All pigs in the area were sampled with the exception of suckling piglets and advanced pregnant sows (n = 304). The samples were analyzed by the Enzyme Immuno Electro Transfer Blot (EITB) test. Resulting data was evaluated to determine the risk factors and a stocastic simulation was used to asses the real prevalence, using functions that generate random numbers that followed beta binomial distributions. The level of infection in Nueva Esperanza was significantly lower to those found in Turpo and Matapuquio (p<0.05). No statistical differences were found due to sex. There was a perfect direct correlation between age and the prevalence of porcine cysticercosis (rs=1). The logistic regression showed that location and age represented risk factors asociated with the disease (p<0.0001). Serologic results indicated that the general prevalence was 47.3 ± 5.6%, while prevalence for Nueva Esperanza was 26.5 ± 7.6, for Turpo was 72.3 ± 9.5, and for Matapuquio was 54.0 ± 10.5%. The real prevalence for all three villages would be of 23%, whereas 96% of the observations were between 17 and 29%. It is concluded that porcine cysticercosis in Andahuaylas villages is a public health problem